Assessing Stability of Transition Metal Nitrides in Aqueous Environments: The Case of Molybdenum, Iron, Vanadium and Nickel Nitride. Issue 4 (9th March 2020) - Matanovic, Ivana; Garzon, Fernando H.
Abstract : Analysis of the MoN, Mo2 N, VN, Fe2 N, Fe4 N, Ni3 N stability in the aqueous media was performed based on the thermodynamic data available in HSC Chemistry software. Our analysis show that among all the studied nitrides, cubic Mo2 N is the most resistant while cubic VN is the least resistant to oxidation and decomposition. The change in temperature up to 100 °C does not significantly influence the formation potentials of transition metal oxides from nitrides; however, pH significantly affects the stability of the studied transition metal nitrides. In the case of Mo2 N, MoN, and VN changing pH from acidic to neutral and alkaline decreases the stability of the nitrides and the oxide formation potentials shift to more negative values. Based on thermodynamics, orthorhombic Fe2 N should be stable only in alkaline conditions, while cubic Fe4 N and hexagonal Ni3 N should be the most stable at pH ∼ 7 and pH ∼ 9. Changing pH from these values decreases the stability of both Fe4 N and Ni3 N and the formation of oxy-, hydroxy- species becomes thermodynamically more favorable. The limited stability of the metal nitrides places severe constraints for their use in aqueous electrocatalytic applications.